Estudio de prefactibilidad para la instalación de una planta extractora de aceite crudo de palma aceitera ( Elaeis guineensis jacq), en la provincia de Alto Amazonas - Gonzales Ramirez, Abraham (2013)
The project's initiative partly meet the demand for crude oil in our country, considering that we are deficient in oils and fats and their importance is to constitute an agro-industrial crop, occupying significant amount of labor, both in the field phase, and its production and industrialization phase, with the main food market refineries in our country and as potential markets, producers of feed and in the production of biodiesel. Dining extracting crude palm oil is in the hands of factories located in the regions of San Martin, Ucayali and Loreto, counting each with areas of raw material supply, these campantes are producing the domestic supply of oit crude palm, showing great performance with the development of the activity, and about 200 000 hectares is needed in production with an average yield of 3,5 TM/ha/year of oil to meet domestic demand for food and biodiesel in Peru. The Palm Producers Association of the province of Alto Amazonas behind the project has 1 555,5 hectares of oíl palm, of which 1077,5 hectares are in production and 478 hectares are growing and with a projected yield average of 13,56 TM/ha/year overall for 2013. The project will initiate its activities 2016 with 18879,13 MT of palm fruitt availability of raw materials will be supplied by their partners. The plant will start its activities using the 43, 70% of its installed capacity of processing, representing 18879,13 TM of fresh fruit bunches (RFF), the same will be increased year by year, at the end of the horizon project capacity utilization of the plant wi11 be 87 ,25% and may make future extensions of the field crop. The location of the extraction plant will be located in the Town Centre Retail Miguel Grau province of Alto Amazonas, Loreto Region, an area of 50 000 m2 The investment of the project amounts to 12,224 531 PEN, where 35, 19% will be assumed with the capital and 64,81% will be financed by the Regional Government of Loreto, through the Regional Agricultura! Credit Program (PROCREA), at a rate of 6%. lndicators of financia! and economic evaluation of the project show a positive return, such as: VANE = 32 436 137,36; VANF = 36 892 206,16; TIRE= 36,58 %; TIRF = 80,05 %; RB/CE = 1,26; RB/CF = 1,31; PRIE = 3,5 years; PRIF = 1,6 years. By sensitizing the project assuming the variation of factors: falling price of crude oil by 20%, decreased volume collection of fresh fruit by 30%, reduction in the rate of extraction of crude oil 2%; an interest rate of 12% for credit evaluation indicators still show favorable performance values. xiv